FIRST DATA ON TRACE METAL LEVEL AND BEHAVIOUR IN TWO MAJOR ARCTIC RIVER-ESTUARINE SYSTEMS (OB AND YENISEY) AND IN THE ADJACENT KARA SEA, RUSSIA - Dai M.H.; Martin J.M. (My University, 1995)
Dissolved and colloidal trace element concentrations (Cd, Cu, Fe, Ni and Pb) were determined in the Ob and Yenisey river-estuary systems and in the adjacent Kara Sea in September 1993. The data show a natural low concentration level of ‘dissolved’ (< 0.4 μm) trace metals (Cd, Cu, Fe, Ni and Pb) in the two rivers and in the Kara Sea as compared to world unpolluted rivers and the central Arctic Ocean, suggesting that the region studied is pristine with respect to trace metals. The pathway of trace metals transported from rivers to the ocean seems to be complicated, and largely influenced by biogeochemical processes taking place in the estuarine mixing zone. Colloidal material (104 Daltons-0.4 μm), in addition to its significant contribution to the so-called ‘dissolved’ fraction, has been shown to play a fundamental role in determining the behaviour of both conservative and non-conservative trace metals during estuarine mixing. Hence, colloids may control to a large extent the fate of ‘dissolved’ trace metals as well as their net input from the rivers to the Kara Sea.